Prospek Pengembangan Usahatani Kakao di Desa Pangsan, Kecamatan Petang, Kabupaten Badung - RAMADHANI, RISTA ULVIA; BUDIASA, I WAYAN; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Prospect of Cocoa Farming Development in Pangsan Village, Petang Sub- District of Badung Regency Cocoa plays an important role for the national economy, especially opening employment opportunities, sources of income, and foreign exchange. The objectives of this research are: to investigate the suitability of land for cocoa farming in Pangsan Village, financial feasibility of cocoa farming in Pangsan Village, seen from investment criteria, and market prospect of cocoa commodity of Pangsan Village production. The analysis used in this research is investment criteria method including NPV, IRR, and Net B/C for financial feasibility analysis, while land suitability and market prospect are analyzed descriptively and qualitatively. The findings of the study showed that : land in Pangsan Village is appropriate (S2) for cocoa farming and it has low productivity compared to cocoa productivity in Bali and Indonesia, cocoa farming in Pangsan village which is intercropped with coconut and banana trees is financially feasible to be cultivated, with NPV of Rp 29.454.914,86, IRR of 38%, and Net Benefit Cost Ratio (Net B/C) of 7,68, and the market prospect of cocoa products in Pangsan Village is not prospective for foodstuff, because the product of cocoa produced is not fermented and not certified.